MODEL OF ISLAMIC EDUCATION MANAGEMENT IN FORMING STUDENTS MORALS: STUDY RESEARCH IN MIDDLE SCHOOL OF PUSPANEGARA CITEUREUP - Muhammad Baghir (Sekolah Tinggi Agama Islam Al Hidayah Bogor, 2020)
This study aims to determine the ideal pattern of Islamic education management in shaping student morals. The approach used is a qualitative approach, data collection techniques using the method of observation, interviews and documentation. Data analysis techniques using an interactive model of data reduction, data presentation and verification. The data validity technique uses an extension of participation, perseverance of observation, and triangulation. The results obtained from the study are; 1) the entire management process (planning, implementation, organization, leadership, and supervision / evaluation) of moral education must involve all elements of the school, students' parents or stakeholders. 2) the principal's leadership in carrying out its functions determines the success of education management in forming the morals of students at school. 3) the ability of all subject teachers and extracurricular advisers in integrating learning material with Islamic teaching values. 4) the formation of Islamic culture in the school environment supported by adequate facilities and infrastructure, a conducive school environment and teacher cohesiveness in each activity.